High-acetyl-degree chitosan oligosaccharide and preparation method thereof

By mechanically treating chitin and catalyst, the problem of difficulty in preparing chitosaccharides and lowering acetyl degree is solved, and efficient preparation of chitosaccharides with high acetyl degree is achieved, which improves its application value.

CN119528996APending Publication Date: 2025-02-28JIHUA LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411831049.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing chitosan oligosaccharide preparation methods have problems of preparation and a decrease in acetyl degree, making it difficult to directly obtain chitosan oligosaccharides with high acetyl degree.

Method used

By mixing chitin with the catalyst and performing mechanical treatment, the instantaneous stretching action during the mechanical treatment and the catalyst cutting off the glycosidic bonds can be used to degrade chitin to produce chitin oligosaccharides.

Benefits of technology

The efficient preparation of chitosaccharides with high acetyl degree is achieved in almost anhydrous state, avoiding the problem of acetyl degree reduction, and no secondary reaction is required to increase the acetyl degree, which improves the application value of chitosaccharides.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528996A_ABST
    Figure CN119528996A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of chitosan oligosaccharide preparation, and mainly relates to high-acetyl-degree chitosan oligosaccharide and a preparation method thereof. The preparation method comprises the following steps: mixing chitin and a catalyst, and carrying out mechanical treatment to obtain a mixture; and dispersing and dissolving the mixture in water, filtering to remove the catalyst, neutralizing filtrate, removing impurities, and drying to obtain the high-acetyl-degree chitosan oligosaccharide. According to the method, the chitin is degraded through the instant stretching effect of the mechanical treatment process on the chitin and the cutting effect of the catalyst on the chitin glucosidic bond, the selectivity higher than that of liquid acid is achieved for producing the chitosan oligosaccharide, monomers and disaccharide in the prepared chitosan oligosaccharide are few, and the 3-7 sugar content is high. Moreover, the preparation method provided by the invention can be carried out in a solid state, the deacetylation reaction can be completed without sufficient water, the deacetylation reaction is almost not carried out, the acetylation structure in the chitin is not damaged, and the chitosan oligosaccharide with high acetylation degree can be produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of chitosan oligosaccharide preparation, and mainly to a high-acetylation chitosan oligosaccharide and a preparation method thereof. Background Art

[0002] Chitosan oligosaccharide is a 2-10 unit oligosaccharide composed of N-acetylglucosamine connected by β-1,4 glycosidic bonds. It is water-soluble and easily dispersed and absorbed. It is widely used in food, medicine, agriculture and other fields. As a functional oligosaccharide, it has multiple functions such as antibacterial, anti-inflammatory, immune protection, intestinal regulation, and plant immune system stimulation.

[0003] The preparation methods of chitosan oligosaccharides include chemical methods, physical methods, bioenzymatic methods and biosynthetic methods. However, the biosynthesis of chitosan oligosaccharides is currently difficult, and the physical method is inefficient. It is often used as an auxiliary method to destroy the crystalline structure of chitin, so these two methods are rarely used. Chemical and bioenzymatic hydrolysis of chitin are the main methods currently used to prepare chitosan oligosaccharides. The chemical method is mainly based on strong acid hydrolysis, supplemented by oxidative degradation. Although this method is relatively easy to prepare chitosan oligosaccharides, the reaction process is difficult to control, the molecular weight distribution of the product is often uneven, and the oligomers are rapidly hydrolyzed into monomers. The bioenzymatic method mainly uses specific chitinase or non-specific enzyme to hydrolyze chitosan. Although this method is mild, the screening and production of enzymes are expensive. In addition, since chitosan is difficult to dissolve in general solvents, there are problems with the accessibility of enzymes and chitosan molecules. The poor solubility of chitosan is the main obstacle to the large-scale production of chitosan oligosaccharides. In addition, the enzymatic reaction can only obtain dimers as the main product, and the proportion of biologically active oligomers (trimers and larger) is relatively small.

[0004] In addition, studies have shown that high-acetylated chitosan oligosaccharides have higher value in various properties than low-acetylated chitosan oligosaccharides. However, the current preparation methods for chitosan oligosaccharides are often accompanied by a decrease in the degree of acetylation, and high-acetylated chitosan oligosaccharides cannot be directly obtained. A secondary reaction is usually required to increase the degree of acetylation of chitosan oligosaccharides. Therefore, it is imperative to develop a highly selective preparation method for chitosan oligosaccharides. Therefore, the existing technology needs to be improved and developed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a high-acetylated chitosan oligosaccharide and a preparation method thereof, aiming to solve the problem that the existing chitosan oligosaccharides are difficult to prepare and are easily accompanied by a decrease in acetylation.

[0006] The technical solution of this application is as follows: In a first aspect, the present application provides a method for preparing high-acetylated chitosan oligosaccharides, which comprises the following steps: The chitosan and the catalyst are mixed and then mechanically treated to obtain a mixture; The mixture is dispersed and dissolved in water, the catalyst is removed by filtration, the filtrate is neutralized, impurities are removed and then dried to obtain the high acetylation chitosan oligosaccharide.

[0007] This application utilizes the instantaneous stretching effect of the mechanical treatment process on chitin and the severing effect of the catalyst on the chitin glycosidic bond to degrade chitin to produce chitosan oligosaccharides. Compared with liquid acid degradation preparation, it has higher selectivity. The monomers and disaccharides in the prepared chitosan oligosaccharides account for a smaller proportion, and 3-7 sugars account for a higher proportion. After preparation, a higher acetylation degree can be retained, and the operation of increasing the acetylation degree by secondary reaction can be omitted, which greatly improves the preparation and application value of chitosan oligosaccharides.

[0008] Furthermore, the preparation method of the catalyst comprises the following steps: The porous solid material is immersed in an acid solution, stirred and mixed, filtered, washed with water and dried.

[0009] Furthermore, the ratio of the porous solid material to the acid solution is 10:3-1:10 (g / ml); the particle size of the porous solid material is 1-150 μm, the porosity is 20%-90%, and the pore size is 0.1-800 nm.

[0010] Furthermore, the concentration of the acid solution is 0.1-16 mol / L, and the stirring time is 2-24 h; The number of times of water washing is 1-3 times, the drying temperature is 30-120° C., and the time is 4-24 hours.

[0011] Furthermore, the particle size of the chitosan is 60-800 mesh, and the mass ratio of the catalyst to the chitosan is 1:0.1-10.

[0012] Furthermore, the steps of neutralizing the filtrate, removing impurities and then drying the filtrate include: The filtrate is neutralized to neutrality, dialyzed through a dialysis membrane to remove the salt produced by neutralization, and then the precipitate is freeze-dried.

[0013] Furthermore, the mechanical treatment time is 4-72h; the mechanical treatment is one or more of ball milling, vibration milling, grinding milling, grinding milling, hammer milling, and air flow milling.

[0014] Furthermore, the porous solid material is one or more of zeolite, activated carbon, diatomaceous earth, mesoporous silica, molecular sieve, and porous ceramics.

[0015] Furthermore, the acid in the acid solution is one of hydrochloric acid, phosphoric acid, lactic acid, sulfuric acid, oxalic acid, acetic acid, formic acid, citric acid, nitrous acid, and hydrofluoric acid, or a mixture of two or more thereof.

[0016] In a second aspect, the present application further provides a high acetylation chitosan oligosaccharide, wherein the chitosan oligosaccharide is prepared by the preparation method of the high acetylation chitosan oligosaccharide as described in the first aspect; The acetylation degree of the high-acetylated chito-oligosaccharide is 75%-100%.

[0017] Beneficial effects: The present application utilizes the instantaneous stretching effect of the mechanical treatment process on chitin and the severing effect of the catalyst on the chitin glycosidic bond to degrade chitin, and has a higher selectivity than liquid acid to produce chitosan oligosaccharides. The monomers and disaccharides in the prepared chitosan oligosaccharides account for a small proportion, and 3-7 sugars account for a high proportion. Moreover, the preparation method provided can be carried out in a solid state, there is no sufficient water for the deacetylation reaction to complete, and almost no deacetylation reaction is carried out, which will not damage the acetylated structure in the chitosan, and can produce chitosan oligosaccharides with a high degree of acetylation. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the infrared spectrum of chitosan oligosaccharides obtained by activated carbon catalytic degradation in Example 1 of the present application.

[0019] Figure 2 This is the nuclear magnetic resonance spectrum of chitosan oligosaccharides obtained by activated carbon catalytic degradation in Example 1 of the present application.

[0020] Figure 3 This is the Maldi-Tof mass spectrum of chitosan oligosaccharides obtained by activated carbon catalytic degradation in Example 1 of the present application. DETAILED DESCRIPTION

[0021] The present application provides a high acetylated chitosan oligosaccharide and a preparation method thereof. To make the purpose, technical solution and effect of the present application clearer and more specific, the present application is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0022] At present, the preparation method of chitosan oligosaccharides is mainly obtained by degradation of chitosan. The rate-determining step of the degradation reaction is the formation of carbon cations. The presence of a small amount of water can complete the degradation reaction. However, the existing preparation methods of chitosan oligosaccharides are mostly carried out under the condition of sufficient water. The acetylation degree of chitosan will be affected during the degradation process. The reason is that water attacking the acetyl group is the rate-determining step of chitosan deacetylation. The degradation reaction and deacetylation reaction diagram of chitosan in an acidic environment are shown below: .

[0023] To address this problem, the present application provides a method for preparing high-acetylated chitosan oligosaccharides in an almost anhydrous state, more specifically, comprising the following steps: S1, mixing chitosan and a catalyst and then subjecting the mixture to mechanical treatment to obtain a mixture; S2. The mixture is dispersed and dissolved in water, the catalyst is filtered out, the filtrate is neutralized and impurities are removed, and high acetylation chitosan oligosaccharide is obtained after drying.

[0024] The present application utilizes the instantaneous stretching effect of the mechanical treatment process on chitin and the severing effect of the catalyst on the chitin glycosidic bond to degrade chitin, and has a higher selectivity than liquid acid to produce chitosan oligosaccharides. The monomers and disaccharides in the prepared chitosan oligosaccharides account for a small proportion, and 3-7 sugars account for a high proportion. Moreover, the preparation method provided can be carried out in a solid state, there is no sufficient water for the deacetylation reaction to complete, and the deacetylation reaction is almost not carried out, and the acetylation structure in the chitosan will not be damaged, and chitosan oligosaccharides with a high degree of acetylation can be produced.

[0025] Furthermore, the method for preparing the catalyst used in step S1 comprises the following steps: S0. Soak the porous solid material in an acid solution, stir and mix, filter, wash and dry the material to obtain a catalyst.

[0026] In the present application, a porous solid material is treated with an acid solution, and the pore structure thereof is utilized to absorb and retain a suitable amount of acid solution, thereby obtaining an acidic solid catalyst. The small amount of acid adsorbed by the porous solid material, combined with the stretching and squeezing effects of mechanical forces under mechanical treatment, can be in close contact with chitin, destroying the glycosidic bonds in the chitin molecules, thereby reducing the molecular weight, and is also conducive to achieving high selectivity in cutting the molecular chains in chitin.

[0027] Before immersion, the porous solid material can be heated to 105-350°C at a rate of 0.1-30°C / min and kept warm for 0.5-48h. The heating treatment is performed to remove moisture that may be adsorbed by the porous solid material to ensure the degree of absorption of the acid solution.

[0028] Furthermore, in step S0, the ratio of the porous solid material to the acid solution is less than 10:1, preferably 10:3-1:10. The ratio is specifically the ratio between the mass of the porous solid material and the volume of the acid solution, in g / ml.

[0029] Furthermore, in step S0, the particle size of the porous solid material is 1-150 μm, preferably 30-100 μm. In the present application, the size of the porous solid material should not be too high or too low. If the size is too large, the contact probability between the acid and chitosan will be reduced, thereby reducing the degradation efficiency of chitosan; if the size is too small, although the specific surface area is greatly increased, more acid will be lost during the preparation process, resulting in a decrease in the acid storage content, which will also reduce the degradation efficiency of chitosan.

[0030] Furthermore, in step S0, the porosity of the porous solid material is 20%-90%, preferably 40%-70%. In the present application, a high porosity will affect the mechanical properties of the porous material, and it is easy to break during mechanical treatment, resulting in uncontrolled degradation; a low porosity will reduce the acid storage capacity, affecting the degradation efficiency of chitin.

[0031] Further, in step S0, the pore size of the porous solid material is 0.1-800nm, preferably 1-500nm, and in the present application, the holes distributed by the porous solid material are too small to reduce the effect of the acid solution and chitin adsorbed, affecting degradation. The hole is too large to reduce the concentration of the acid solution adsorbed, the water content increases, and then the deacetylation degree is increased while degrading the chitin. The present application is conducive to ensuring the degradation effect by controlling the pore size of the porous solid material, while reducing the occurrence of deacetylation. Moreover, chitin has the characteristics of being sticky and easy to form a film when contacting with water, and under the pore size provided, the contact characteristics of chitin can also further control the contact degree of acid solution, and the mixed characteristics of mechanical treatment are matched, and the acid solution is not easy to escape from the pores, and the degradation of the local chitin is not too concentrated, and the glycosidic bond in the chitin with a larger macromolecular chain is continuously maintained to be subjected to a cleavage reaction, ensuring the required degradation effect.

[0032] Furthermore, in step S0, the porous solid material is one or a mixture of two or more of zeolite, activated carbon, diatomaceous earth, mesoporous silica, molecular sieve, and porous ceramics.

[0033] Further, in step S0, the concentration of the acid solution is 0.1-16 mol / L. In the present application, the concentration of the acid solution for immersion preservation will affect the degradation degree of chitin. If the concentration is too low, the effect is not obvious. If the concentration is too high, the degradation degree will be increased and the acetylation degree will be affected. By controlling the acid solution to a suitable concentration, the acid solution preserved in the pores after washing and drying can also be maintained at a suitable concentration, and mechanical treatment is then used to ensure the degradation effect of the contact, which is conducive to improving the preparation efficiency.

[0034] Furthermore, in step S0, the stirring time is 2-24 hours. The degree of absorption of the acid solution by the porous solid material is ensured by controlling the stirring time.

[0035] Furthermore, in step S0, the number of water washing is 1-3 times, the drying temperature is 30-120°C, and the drying time is 4-24 hours. In the present application, by controlling the water washing and drying conditions and coordinating the porosity of the porous solid material used, the acid solution in the catalyst can be kept at an appropriate amount while removing excess acid solution, thereby avoiding affecting the degree of treatment required by the present application.

[0036] Furthermore, in step S0, the acid in the acid solution is one of hydrochloric acid, phosphoric acid, lactic acid, sulfuric acid, oxalic acid, acetic acid, formic acid, citric acid, nitrous acid, and hydrofluoric acid, or a mixture of two or more thereof.

[0037] Furthermore, in step S1, the particle size of chitosan is 60-800 mesh, and the mass ratio of catalyst to chitosan is 1:0.1-10. In the present application, by controlling the particle size of chitosan and the mixing ratio within a suitable range, it is beneficial to improve the degree of interaction with the catalyst and mechanical treatment and ensure the degradation effect.

[0038] Furthermore, in step S1, the mechanical treatment time is 4-72h; the mechanical treatment is one or more of ball milling, vibration milling, milling, grinding, hammer milling, and air flow milling. Among them, one of ball milling, grinding, vibration milling, and milling is more preferred. Specifically, the ball-to-material ratio of ball milling is 2:1-20:1, and the rotation speed is 50-500rpm; the rotation speed of grinding is 100-1000rpm, and the feed ratio is 1 / 10-2 / 3; the vibration frequency of vibration milling is 10-50Hz, and the amplitude is 1-10mm; the grinding pressure of milling is 50-500N, and the rotation speed is 10-60rpm.

[0039] In the present application, large molecular chain chitin can be preferentially degraded by mechanical treatment, because during the mechanical treatment process, long molecular chain chitin is more susceptible to extrusion and contact with the catalyst, while small molecular chain chitin is highly flexible and less likely to be extruded, which is beneficial to maintaining the selectivity and acetylation degree of the prepared chitosan oligosaccharides.

[0040] Specifically, in step S2, the mixture can be dispersed and dissolved by stirring for 0.3-24 hours, or ultrasonically for 1-60 minutes to ensure that the chitosan oligosaccharides therein are fully dissolved in water.

[0041] Furthermore, in step S2, the step of neutralizing and removing impurities from the filtrate and then drying comprises: The filtrate is neutralized to neutrality, and the salt produced by the neutralization is removed by dialyzing through a dialysis membrane. The precipitate is then freeze-dried to obtain high-acetylated chitosan oligosaccharides.

[0042] In the present application, the catalyst used is treated with acid, so there will be some dissolved acid in the filtrate of step S2. Specifically, an appropriate amount of a neutralizing alkali such as NaOH or KOH can be added according to the pH of the filtrate to neutralize the filtrate to neutrality, and the salt produced by acid-base neutralization can be removed by dialyzing with a dialysis membrane to remove impurities, and then the precipitate can be dried by freeze drying or other drying methods to obtain high acetylated chitosan oligosaccharides.

[0043] Specifically, after mechanical treatment, the present invention has a low acid concentration when the mixture is dispersed in water, and no deacetylation reaction occurs without mechanical treatment. Moreover, since the deacetylation efficiency of chitin / chitosan oligosaccharide in an alkaline environment is much higher than that in an acidic environment, the present invention removes the porous solid material in a weakly acidic environment and then performs a neutralization operation, and then separates the chitosan oligosaccharide after neutralization to neutrality by adding an appropriate amount of alkali.

[0044] The present application utilizes a porous solid material and an appropriate amount of acid solution as a solid catalyst, and treats chitin in combination with mechanical treatment. The contact probability between the treatment medium and the solid catalyst and the long molecular chain chitin is greater, and it is easier to break the glycosidic bond. The short molecular chain chitin has high flexibility and is squeezed and has a low contact probability with the treatment medium and the solid catalyst, thereby achieving high selectivity for cutting the molecular chain of chitin, while retaining the required high acetylation degree, and also eliminating the operation of secondary reaction to increase the acetylation degree, thereby greatly improving the preparation and application value of chitosan oligosaccharides.

[0045] The present application also provides a high-acetylation chitosan oligosaccharide, wherein the chitosan oligosaccharide is prepared by the preparation method of the high-acetylation chitosan oligosaccharide as described above.

[0046] Specifically, the present application uses a mechanochemical method for preparation, and the synergistic effect of mechanical grinding and acidic solid catalysts is used to break the glycosidic bonds of sugar polymers, thereby producing oligosaccharides. With the help of ball mills, vibrating mills and other equipment to create a high-intensity mechanical force field, the material is subjected to the high-frequency collision, shearing and friction of the grinding medium, and the polymer crystal structure gradually tends from regular and dense to disordered and loose, the molecular chain stretches, and the internal glycosidic bonds are fully exposed, breaking the original lattice constraints, greatly improving the chemical reaction activity and accessibility; at the same time, the acidic solid catalyst accurately anchors the glycosidic bond site, and cooperates with the mechanical force to gently and efficiently drive the glycosidic bond cleavage reaction to proceed in an orderly manner, avoiding the "degradation out of control" drawbacks of strong acid hydrolysis and the limitation of enzymatic hydrolysis. In laboratory small-scale and pilot-scale studies, it has demonstrated significant advantages such as high product selectivity, few by-products, and easy-to-control reaction conditions, and outlines a new path for the industrialization and green synthesis of chitosan oligosaccharides.

[0047] Furthermore, the acetylation degree of the high-acetylated chito-oligosaccharide is 75%-100%.

[0048] The preparation method provided in the present application is highly selective, and the obtained chito-oligosaccharides retain a high degree of acetylation, reaching 75%-100%, while avoiding the production of excessive monomers and disaccharides, and obtaining chito-oligosaccharides with a higher content of 3-7 sugars, which can reach 92% and above.

[0049] The invention is further described below by means of specific examples.

[0050] Example 1 The method for preparing high-acetylated chitosan oligosaccharides in Example 1 is to catalyze degradation of activated carbon by mechanical treatment, and specifically comprises the following steps: (1) Activated carbon with a particle size of 100 μm, a porosity of 65%, and a pore size of 40 nm was heated to 120° C. at a rate of 10° C. / min and kept at this temperature for 2 h to remove possible adsorbed water. After cooling, 10 g of the activated carbon was added to 30 mL of a 0.1 mol / L hydrochloric acid solution and stirred for 2 h. The excess acid was filtered to remove the excess acid. The filtrate was rinsed with water twice and dried at 40° C. for 4 h to obtain the catalyst of Example 1. (2) The catalyst prepared in step (1) was mixed with chitosan having a particle size of 80 mesh at a mass ratio of 1:2, and then ball milled for 8 h using a planetary ball mill with a ball-to-material ratio of 5:1 and a rotation speed of 160 rpm to obtain a mixture of Example 1; (3) The mixture of step (2) was taken out and dispersed and dissolved in water, and ultrasonicated for 3 minutes to make the chitosan oligosaccharide fully dissolved in water, and the activated carbon was filtered out (recovered), and the chitosan oligosaccharide was collected. The filtrate was neutralized with NaOH, and dialyzed to remove NaCl. The precipitate was freeze-dried to obtain the high-acetylated chitosan oligosaccharide of Example 1, and the conversion rate of chitosan oligosaccharide was tested by weighing. The molecular weight of the obtained high-acetylated chitosan oligosaccharide was tested by size exclusion chromatography.

[0051] Comparative experiment of hydrothermal reaction: With a concentrated hydrochloric acid solution with a concentration of 36% as the reaction medium, 80 mesh chitin was added into a 10-fold concentrated hydrochloric acid solution, and reacted at 60°C for 2h. After neutralization with NaOH, the NaCl was removed by dialyzing with a dialysis membrane for 3d. After freeze-drying the precipitate, the conversion rate of chitosan oligosaccharides was tested by weighing, and the molecular weight of chitosan oligosaccharides was tested by size exclusion chromatography.

[0052] The test results of the conversion rate and molecular weight of chitosan oligosaccharides in Example 1 are shown in Table 1: Table 1

[0053] Example 1 The acetylation degree of chitosan oligosaccharides obtained by activated carbon catalytic degradation was maintained at 90.7%, which was able to effectively maintain the acetylation degree of chitosan oligosaccharides compared with hydrochloric acid hydrothermal reaction degradation.

[0054] The chitosan oligosaccharide obtained by activated carbon catalytic degradation in Example 1 was characterized by infrared chromatograph, and the infrared spectrum measured was as follows: Figure 1 As shown, from Figure 1 It can be seen that the degraded chitosan oligosaccharide shows the typical characteristic peaks of chitosan (938, 1027, 1111, 1160, 1203, 1267, 1312, 1376, 1427, 1553 and 1634 cm-1).-1 The peak at 3000–3500 cm -1 ) and amino groups (NH, 3276 cm -1 ) stretching vibration peak, 1500–1750 cm -1 The peaks at 1634 cm are the stretching vibration peaks of C=O and NH of amide I band. -1 The amide I bands at 1553 cm-1 are respectively attributed to the interaction peaks of the carbonyl and amino groups in the chitin molecular chain (C=O···HN). -1 The amide II band at 1027 cm-1 is attributed to the NH in-plane stretching and bending vibration peaks of the N-acetyl group. -1 The peaks at 400 nm are attributed to the stretching vibration peaks of COC. The positions of these peaks and the relative proportions of each peak indicate that degradation has not caused damage to the structure of chitin molecular units.

[0055] The chitosan oligosaccharide obtained by activated carbon catalytic degradation in Example 1 was subjected to nuclear magnetic resonance testing, and the measured nuclear magnetic spectrum was as follows: Figure 2 As shown, the proton signal of H-1 is at 4.4-5.1 ppm, the proton signal of H-3 / 4 / 5 / 6 is at 3.2-3.8 ppm, the proton signal of H-2 is at 2.7-3.2 ppm, and the proton signal of H-7 is near 2.0 ppm. The methyl peak (H-7) of the acetylamino group is relatively strong, indicating that the acetylation degree of chitosan oligosaccharide is high. The signal attribution of chitosan oligosaccharide at each position is basically consistent with that of chitin.

[0056] The chitosan oligosaccharides obtained by activated carbon catalytic degradation in Example 1 were analyzed using Maldi-Tof mass spectrometry. The ion flow results showed that there were many potential chitosan oligosaccharide peaks. The corresponding potential oligosaccharide peaks in the ion flow were further analyzed one by one. The results are as follows: Figure 3 As shown, the corresponding peak contains fully acetylated chito-oligosaccharides with a degree of polymerization of 2-7 and a small amount of partially deacetylated chito-oligosaccharides.

[0057] Example 2 The method for preparing high acetylated chitosan oligosaccharide in Example 2 is to catalyze degradation by mechanically treating zeolite, and specifically comprises the following steps: (1) 20 g of zeolite with a particle size of 30 μm, a porosity of 40%, and a pore size of 1 nm was added to 20 mL of a 1.84 mol / L sulfuric acid solution and stirred for 24 h. The excess acid was filtered to remove the excess acid. The filtrate was rinsed with water once and dried at 40° C. for 8 h to obtain the catalyst of Example 2. (2) The catalyst prepared in step (1) was mixed with chitosan with a particle size of 80 mesh at a mass ratio of 1:2, and then ground using a grinder for 12 hours at a speed of 240 rpm and a feed ratio of 1 / 3 to obtain a mixture of Example 2; (3) The mixture of step (2) was taken out and dispersed and dissolved in water, and ultrasonicated for 3 minutes to make the chitosan oligosaccharide fully dissolved in water, and the zeolite was filtered out (recovery), and the chitosan oligosaccharide was collected. The filtrate was neutralized with NaOH, and dialyzed to remove NaCl. The precipitate was freeze-dried to obtain the high-acetylated chitosan oligosaccharide of Example 2, and the conversion rate of chitosan oligosaccharide was tested by weighing. The molecular weight of the obtained high-acetylated chitosan oligosaccharide was tested by size exclusion chromatography.

[0058] Comparative experiment of hydrothermal reaction: With a concentrated sulfuric acid solution with a concentration of 98% as the reaction medium, 80 mesh chitin was added into a concentrated sulfuric acid solution with a mass 10 times that of the solution, and the reaction was carried out at 60°C for 2.5 hours. After neutralization with NaOH, the chitosan was dialyzed for 3 days using a dialysis membrane to remove NaSO4. After the precipitate was freeze-dried, the conversion rate of chitosan oligosaccharides was tested by weighing, and the molecular weight of chitosan oligosaccharides was tested using size exclusion chromatography.

[0059] The test results of the conversion rate and molecular weight of chitosan oligosaccharides in Example 2 are shown in Table 2: Table 2

[0060] It can be found that the acetylation degree of chitosan oligosaccharides obtained by zeolite catalytic degradation in Example 2 is maintained at 90.9%, which can effectively maintain the acetylation degree of chitosan oligosaccharides compared with the hydrothermal reaction degradation by sulfuric acid.

[0061] Example 3 The method for preparing high acetylated chitosan oligosaccharide in Example 3 is to catalyze degradation by mechanically treating porous ceramics, and specifically comprises the following steps: (1) 15 g of porous ceramic with a particle size of 75 μm, a porosity of 55%, and a pore size of 120 nm was added to 30 mL of a 7.35 mol / L phosphoric acid solution and stirred for 24 h. The excess acid was filtered to remove the excess acid. The filtrate was rinsed with water twice and dried at 40° C. for 6 h to obtain the catalyst of Example 3. (2) The catalyst prepared in step (1) was mixed with chitosan with a particle size of 80 mesh at a mass ratio of 1:1, and then subjected to vibration milling for 12 hours at a vibration frequency of 20 Hz and an amplitude of 5 mm to obtain a mixture of Example 3; (3) The mixture of step (2) was taken out and dispersed and dissolved in water, and ultrasonicated for 3 minutes to make the chitosan oligosaccharide fully dissolved in water, and the porous ceramic was filtered to remove (recovery), and the chitosan oligosaccharide was collected. The filtrate was neutralized with NaOH, and then dialyzed to remove Na3PO4. The precipitate was freeze-dried to obtain the high-acetylated chitosan oligosaccharide of Example 3, and the conversion rate of chitosan oligosaccharide was tested by weighing. The molecular weight of the obtained high-acetylated chitosan oligosaccharide was tested by size exclusion chromatography.

[0062] Comparative experiment of hydrothermal reaction: Using concentrated phosphoric acid solution with a concentration of 85% as the reaction medium, 80 mesh chitosan was added into 10 times phosphoric acid, and reacted at 60°C for 4 hours. After neutralization with NaOH, the chitosan was dialyzed for 3 days with a dialysis membrane to remove Na3PO4. After freeze-drying the precipitate, the conversion rate of chitosan oligosaccharides was tested by weighing, and the molecular weight of chitosan oligosaccharides was tested by size exclusion chromatography.

[0063] The test results of the conversion rate and molecular weight of chitosan oligosaccharides in Example 3 are shown in Table 3: Table 3

[0064] It can be found that the acetylation degree of chitosan oligosaccharides obtained by porous ceramic catalytic degradation in Example 3 is maintained at 91%, which is more effective than the hydrothermal reaction degradation of phosphoric acid in maintaining the acetylation degree of chitosan oligosaccharides.

[0065] Example 4 The method for preparing high acetylated chitosan oligosaccharide in Example 4 is to catalyze degradation by mechanically treating diatomaceous earth, and specifically comprises the following steps: (1) 15 g of diatomaceous earth with a particle size of 38 μm, a porosity of 70%, and a pore size of 50 nm was added to 60 mL of 8 mol / L lactic acid solution and stirred for 8 h. The excess acid solution was filtered to remove the excess acid solution. The filtrate was rinsed with water twice and dried at 40° C. for 24 h to obtain the catalyst of Example 4. (2) The catalyst prepared in step (1) was mixed with chitosan having a particle size of 80 mesh at a mass ratio of 1:1, and then ground for 12 h using a grinding machine at a grinding pressure of 200 N and a rotation speed of 40 rpm to obtain a mixture of Example 4; (3) The mixture of step (2) was taken out and dispersed and dissolved in water, and ultrasonicated for 3 minutes to make the chitosan oligosaccharide fully dissolved in water, and the porous ceramic was filtered out (recovery), and the chitosan oligosaccharide was collected. The filtrate was neutralized with NaOH, and then dialyzed to remove sodium lactate. The precipitate was freeze-dried to obtain the high-acetylated chitosan oligosaccharide of Example 3, and the conversion rate of chitosan oligosaccharide was tested by weighing. The molecular weight of the obtained high-acetylated chitosan oligosaccharide was tested by size exclusion chromatography.

[0066] Comparative experiment of hydrothermal reaction: Using 88% lactic acid solution as the reaction medium, 80 mesh chitosan was added into 10 times lactic acid, and the mixture was reacted at 60°C for 4 hours. After neutralization with NaOH, the mixture was dialyzed with a dialysis membrane for 3 days to remove sodium lactate. After freeze-drying the precipitate, the conversion rate of chitosan oligosaccharides was tested by weighing, and the molecular weight of chitosan oligosaccharides was tested by size exclusion chromatography.

[0067] The test results of the conversion rate and molecular weight of chitosan oligosaccharides in Example 4 are shown in Table 4: Table 4

[0068] It can be found that the acetylation degree of chitosan oligosaccharides obtained by diatomaceous earth catalytic degradation in Example 4 is maintained at 91%, which can effectively maintain the acetylation degree of chitosan oligosaccharides compared with lactic acid hydrothermal reaction degradation.

[0069] Example 5 The preparation method of high-acetylated chitosan oligosaccharide in Example 5 is basically the same as that in Example 1, except that the particle size of the activated carbon in Example 5 is 8 μm, the porosity is 65%, and the pore size is 40 nm. The high-acetylated chitosan oligosaccharide in Example 5 is obtained through preparation.

[0070] Example 6 The preparation method of high-acetylated chitosan oligosaccharide in Example 6 is basically the same as that in Example 1, except that the particle size of the activated carbon in Example 6 is 100 μm, the porosity is 20%, and the pore size is 40 nm. The high-acetylated chitosan oligosaccharide in Example 6 is obtained through preparation.

[0071] Example 7 The preparation method of high acetylated chitosan oligosaccharide in Example 7 is basically the same as that in Example 1, except that the particle size of Example 7 is 100 μm, the porosity is 92%, and the pore size is 40 nm. The high acetylated chitosan oligosaccharide in Example 7 is obtained through preparation.

[0072] Example 8 The preparation method of high acetylated chitosan oligosaccharide in Example 8 is basically the same as that in Example 1, except that the particle size of Example 8 is 100 μm, the porosity is 65%, and the pore size is 800 nm. The high acetylated chitosan oligosaccharide in Example 8 is obtained through preparation.

[0073] Comparative Example 1 The preparation method of chitosan oligosaccharide in Comparative Example 1 is basically the same as that in Example 1, except that Comparative Example 1 uses non-porous abrasives with the same particle size (solid silica microspheres with a particle size of 100 μm, which have been soaked in acid and washed with water) for mechanical treatment to obtain the chitosan oligosaccharide in Comparative Example 1.

[0074] The chitosan oligosaccharides prepared in Example 1, Examples 5-8 and Comparative Example 1 were weighed to test the conversion rate of chitosan oligosaccharides, and the molecular weight of the prepared high-acetylated chitosan oligosaccharides was tested using size exclusion chromatography. The test results of conversion rate and molecular weight are shown in Table 5: Table 5

[0075] By comparison, it can be found that the conversion rate of chitosan oligosaccharides can be significantly improved by using porous solid materials soaked in acid solution, and the size and porosity of the porous solid materials will also affect the conversion rate of chitosan oligosaccharides. The conversion rates of the embodiments with smaller sizes and lower porosity are significantly lower, and the embodiments with higher porosity have partial fragmentation, uncontrolled degradation, and the proportion of low molecular weight chitosan oligosaccharides increases, while the acetylation degree decreases. And as the pore size increases, the acetylation degree also decreases. In Comparative Example 1, the solid silica microspheres cannot store acid solution, the conversion rate of chitosan oligosaccharides is low, and the degradation effect is poor. By controlling the pore structure of the porous solid material, it is beneficial to keep the chitosan oligosaccharides at the required high acetylation degree while ensuring the degradation effect.

[0076] Through the preparation method provided in the present application, it is possible to obtain chitosan oligosaccharides with a higher content of 3-7 sugar while maintaining a higher conversion rate, with a low deacetylation degree and retaining the required high acetylation degree. The operation of secondary reaction to increase the acetylation degree can also be omitted, thereby greatly improving the preparation and application value of chitosan oligosaccharides.

[0077] The present application can avoid uncontrolled degradation and effectively contact chitosan during mechanical treatment by adsorbing acid solution into porous solid materials to degrade chitosan; during the mechanical treatment, the porous solid material is acid-catalyzed and preferentially contacts chitosan with large molecular chains, so that the molecular weight of the product is selective, the production of excessive monomers and disaccharides is avoided, and a higher content of 3-7 sugars can be obtained; the water content is low during the mechanical treatment process, the deacetylation reaction of chitosan oligosaccharides is avoided, and the ratio of acetylamino groups on each sugar is maintained. The method is selective for both the degree of acetylation and the number of sugars, and chitosan oligosaccharides with a high degree of acetylation can be obtained.

[0078] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made according to the above description, and all these improvements and changes should fall within the scope of protection of the present application.

Claims

1. A method for preparing high acetylated chitosan oligosaccharide, characterized in that: The following steps are involved: The chitosan and the catalyst are mixed and then mechanically treated to obtain a mixture; The mixture is dispersed and dissolved in water, the catalyst is removed by filtration, the filtrate is neutralized, impurities are removed and then dried to obtain the high acetylation chitosan oligosaccharide.

2. The method for preparing high acetylated chitosan oligosaccharide according to claim 1, characterized in that: The preparation method of the catalyst comprises the following steps: The porous solid material is immersed in an acid solution, stirred and mixed, filtered, washed with water and dried.

3. The method for preparing high acetylated chitosan oligosaccharide according to claim 2, characterized in that: The ratio of the porous solid material to the acid solution is 10:3-1:10 (g / ml); the particle size of the porous solid material is 1-150 μm, the porosity is 20%-90%, and the pore size is 0.1-800 nm.

4. The method for preparing high acetylated chitosan oligosaccharide according to claim 3, characterized in that: The concentration of the acid solution is 0.1-16 mol / L, and the stirring time is 2-24 h; The number of times of water washing is 1-3 times, the drying temperature is 30-120° C., and the time is 4-24 hours.

5. The method for preparing high acetylated chitosan oligosaccharide according to claim 1, characterized in that: The particle size of the chitosan is 60-800 meshes, and the mass ratio of the catalyst to the chitosan is 1:0.1-10.

6. The method for preparing high acetylated chitosan oligosaccharide according to claim 1, characterized in that: The steps of neutralizing the filtrate, removing impurities and then drying the filtrate include: The filtrate is neutralized to neutrality, dialyzed through a dialysis membrane to remove the salt produced by neutralization, and then the precipitate is freeze-dried.

7. The method for preparing high acetylated chitosan oligosaccharide according to claim 1, characterized in that: The mechanical treatment time is 4-72h; the mechanical treatment is one or more of ball milling, vibration milling, grinding milling, grinding milling, hammer milling, and air flow milling.

8. The method for preparing high acetylated chitosan oligosaccharide according to claim 3, characterized in that: The porous solid material is one or more of zeolite, activated carbon, diatomaceous earth, mesoporous silica, molecular sieve, and porous ceramics.

9. The method for preparing high acetylated chitosan oligosaccharide according to claim 4, characterized in that: The acid in the acid solution is one of hydrochloric acid, phosphoric acid, lactic acid, sulfuric acid, oxalic acid, acetic acid, formic acid, citric acid, nitrous acid, and hydrofluoric acid, or a mixture of two or more thereof.

10. A high acetylation chitosan oligosaccharide, characterized in that: Prepared by the preparation method of high acetylated chitosan oligosaccharide according to any one of claims 1 to 9; The acetylation degree of the high-acetylated chito-oligosaccharide is 75-100%.